Community-Based Participatory Research: Toward Eliminating Rural Health Disparities - Barbara Ann Graves (Rural Nurse Organization; Binghamton University, 2012)
The National Healthcare Disparities Report (NHDR) (2008) tracks and documents access to healthcare as well as quality of healthcare. This report provides information to policymakers, clinicians, administrators, and community leaders for the improvement of healthcare services. From this report it is apparent that disparities in healthcare still exist and that many opportunities for improvement remain across racial, ethnic, socioeconomic, and geographical groups.